2014
DOI: 10.1186/bf03352238
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic and rock magnetic studies of Cretaceous rocks in the Eumsung basin, Korea

Abstract: Paleomagnetic results are obtained from 41 sites from the Chopyeong Formation within the Eumsung basin, located along the northern boundary of the Ogcheon Belt, Korea. The Chopyeong Formation, deposited in early Cretaceous, yields the mean direction of D/I = 347.8• /57.3• ) before tilt correction, and D/I = 0.7• /61.7• ) after tilt correction. The parameter estimating fold test and the stepwise unfolding test of the red bed and greenish mudstone of the Chopyeong Formation yield the maximum value of k at 21.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…2). Various lines of evidence, including the aforementioned molluscs, ostracods, and palynomorphs suggest that the Hayang Group is Aptian to early Albian in age (Choi, 1985(Choi, ,1989Yi et al, 1994 Ar (Doh and Kim, 1994).…”
Section: Geological Settingmentioning
confidence: 99%
“…2). Various lines of evidence, including the aforementioned molluscs, ostracods, and palynomorphs suggest that the Hayang Group is Aptian to early Albian in age (Choi, 1985(Choi, ,1989Yi et al, 1994 Ar (Doh and Kim, 1994).…”
Section: Geological Settingmentioning
confidence: 99%
“…The stability of the observed paleomagnetic directions for the sites 3 and 6 (Fig. 4a) further ascertains that the secondary magnetization is not attributed to a Recent weathering, as suggested by Doh et al (1999).…”
Section: Discussionmentioning
confidence: 73%
“…However, it is also considered to be unlikely because the secondary magnetization has been observed from both hematite and magnetite: Doh et al (1999) claimed that a weathering process does not form hematite and magnetite at the same time. The stability of the observed paleomagnetic directions for the sites 3 and 6 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier paleomagnetic studies on Mesozoic to Tertiary rocks from the Korean Peninsula showed vertical rotations with respect to China (e.g., Lee et al 1987;Kim and Van der Voo 1990;Doh and Piper 1994;Zhao et al 1994Zhao et al , 1999Doh et al 1999Doh et al , 2002Lee et al 1999;Zhao et al 1999;Uno 2000;Park et al 2003Park et al , 2005Park et al , 2007Kim et al 2009). Then, viable solutions to explain the various degrees of vertical rotations observed in previous paleomagnetic investigations required that individual geologic terranes of the Korean Peninsula formed in Mesozoic to Tertiary experienced different degrees of vertical rotations.…”
Section: Discussionmentioning
confidence: 99%
“…A robust reconstruction of Laurasia is possible only when Mesozoic paleogeography of the Korean Peninsula is well established, bridging the two sides of the Chinese cratons (e.g., Lee et al 1987;Kim and Van der Voo 1990;Zhao et al 1994Zhao et al , 1999Doh et al 1999Doh et al , 2002Park et al 2003Park et al , 2005Park et al , 2007Kim et al 2009). The primary goal of paleomagnetism is to uncover information about the history of deformation and vertical rotations in geologic units.…”
Section: Introductionmentioning
confidence: 99%